Sovereign wealth funds, productivity and people: The impact of Norwegian government pension fund - global investments in the UK - Marc Goergen; Noel O'Sullivan; Geoffrey Wood; Marijana Baric (2018)
Sovereign Wealth Funds (SWFs) have an increasing presence in the global financial ecosystem, principally through their investments in equities, which, in turn, may influence HRM. This study examines the influence of the world’s largest SWF, the Norwegian Government Pension Fund-Global (NGPF-G), on employment in its UK investee firms. We find that firms with NGPF-G investment are significantly less likely to reduce their demand for labour, more specifically in the immediate aftermath of the 2008 financial crisis. When a drop in the demand for labour does occur, it is less extreme when compared to similar organizations without a NGPF-G shareholding, and this is evident even in the case of relatively small NGPF-G investments. These findings are in line with the fund’s objective of promoting corporate sustainability and Norwegian values. We draw out the key implications of our findings for HR practice.